Unusual salting effects in ionic liquid solutions - Nanda, Raju; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
Unusual salting effects of salting-out agents like LiCl and NaCl and salting-in agents like LiClO4 and NaClO4 in ionic liquid solutions are reported. It is observed that the salting behavior in water can be altered in the presence of ionic liquids. It is demonstrated that the salting-in agents in the presence of the ionic liquids with higher alkyl chain can display unusual fall and rise in the viscosity of the systems. On the other hand, no change in the behavior of the salting-out agents is noted in these ionic liquids. A tentative explanation is proposed for the observed viscosity data in these systems.
Keywords: Cationic ring; ionic liquids; Salting effects; viscosity

Experimental signature of microheterogeneity in ionic liquid-H2O systems and their perturbation by adding Li+ salts: a pulsed gradient spin-echo NMR approach - Nanda, Raju; Rajamohanan, P. R.; Kumar, Anil (Chemphyschem, 2015)
Distinct microheterogeneity has been observed in the [OMIM]Br-H2O system, which is interestingly perturbed by the addition of Li+ salts, indicating unusual diffusivity of [OMIM]Br and H2O molecules. However, the diffusional dynamics of water clusters show contrasting salting behavior at higher concentrations of Li+ salts, following the classical salting phenomenon in lower amounts. In contrast, the existing microheterogeneity in the [BMIM]Br-H2O system is weak enough to show any perturbation caused by the Li+ salts on the NMR time scale.
Keywords: ionic liquids; lithium; microheterogeneity; salt effect; viscosity

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity

Phase behavior, diffusion, structural characteristics, and pH of aqueous hydrophobic ionic liquid confined media: insights into microviscosity and microporsity in the [C(4)C(4)im][NTf2] + water system - Nanda, Raju; Kumar, Anil (Journal of Physical Chemistry B, 2015)
We present our studies on the physicochemical properties of water confined in Dibutylimidazolium bis(trifluoromethanesulfonylimide) ([C(4)C(4)im][NTf2]) reverse micelles through the NMR relaxation measurements that provide us an understanding of microviscosity and pH in the confined condition. We present experimental results on phase behavior, diffusion, structural characteristics and pH in aqueous ionic liquid-confined media. The ternary phase diagram was constructed by the cloud point measurements and the microheterogeneous regions were detected by the measurement of bulk viscosity and diffusion coefficients of K-4[Fe(CN)(6)] inside the homogeneous microemulsion systems through the cyclic voltammetric (CV) measurements. The size of the microemulsion systems was characterized by the dynamic light scattering (DLS) method. The H-1 NMR spectra of homogeneous microemulsion systems were taken which indicates the presence of bound and free water molecules inside the microemulsion system. The NMR spinlattice relaxation time (T-1) of water molecules in its homogeneous microemulsion systems were measured and the reorientational correlation time (t(c)) of water molecules obtained from it indicates that the fluidity of homogeneous confined media decreases with the decrease in the composition of water. Microviscosity of the aqueous confined media was calculated from the measured T-1 relaxation time values by applying the DebyeStokes equation and correlated with the bulk viscosity of the samples. It was observed that both the microviscosity and bulk viscosity show inverse relationship. The fraction of bound and free water molecules were calculated from the measured T-1 values. NMR spinspin relaxation time (T-2) of water molecules in its homogeneous microemulsion systems were measured with the varying pH of the aqueous core. A change in the T-2 relaxation time of the water proton was observed proposing an exchange of proton between the H2O and -OH group of the TX-100 molecules. Finally, methyl orange (MO) was used as a UVvis spectrophotometric molecular probe and the measured lambda(max) values of the probe were used for the detection of micropolarity of the homogeneous aqueous confined media and was found to be increase with the increase in the size of the confined media.